2 - Les biens d'équipement dans l'industrie algérienne - THIERRY, S. P. (Africa Development, 1981)
The role of any industrial activity is to produce either final consu mer goods, production goods (for the use by the intermediary productive sectors) or equipment goods (installations and machines which could last more than a year and which are used by the production units themselves). The author's intention in this article is to analyse the role of the equiment goods sector in the process of capital accumulation, using in particular a historical approach. He first points out that this is a sector where the state had to import almost everything. Hence the importance of analysing the place of industrial equipment goods in national development plans and of trying to find the reasons for such a massive resort to the world market. According to the author, the following problems are worthy of deep analy sis if the obstacles to the emergence and development of such a sector are to be identified: Firstly, the issue of scale and its effect, secondly the pro blems related to the method of implementation and thirdly the nature of the technologies used. He then proposes to concentrate his study on the internal factors related to these problems. There are two reasons for this approach: Firstly because most studies of these problems have concentrated on external factors such as the dependence on the world market and international corporations. Secondly, the author's approach will make it easier to identify those decisions and functionning processes of national structures which could explain the difficulties of the past as well as help plan for future development. Then the author goes on analysing the categories of goods and their equilibrum, giving the elements which are to be taken into account and their relative importance in the implementation of any industrial pro ject. Given this theoretical frame, he makes an evaluation of the present situation of the country in terms of employment (needs of the on-going industrial programme) and of resources (capacity of the national structures and import). He then concludes that the annual needs of industrial projects are three times more important than the annual output of the engineering and electric industries of Algeria. Therefore the contribution of the national production to the implementation of new industrial projects is relatively weak. In any case it seems that the Algerian engineering and electrical industries could have increased fourfold their final production in terms of value with «policy of equipment goods based on import substitution since both their production process and the scale effects allows for this. After dealing with the choice of technology and technological conception, the place of equipment goods in the 1980-1990 planning, the author conclu des his article with the findings that the production processes and the tech nology used in the 1962-1978 plans for the industrial public sector are to be considered as consequences rat er than causes of the weaknesses of the development of the equipment goods production sector. Nevertheless the industrial programme3 of the earlier period (1962-78) have created favou rable conditions for the development of the equipment goods sector.